Design of a new urban wind turbine airfoil using a pressure-load inverse method - Henriques, J.C.C. (2013)
This paper presents the design methodology of a new wind turbine airfoil that achieves high performance in urban environment by increasing the maximum lift. For this purpose, an inverse method was applied to obtain a new wind turbine blade section with constant pressure-load along the chord, at the design inlet angle. In comparison with conventional blade section designs, the new airfoil has increased maximum lift, reduced leading edge suction peak and controlled soft-stall behaviour, due to a reduction of the adverse pressure gradient on the suction side. Wind tunnel experimental results confirmed the computational results.